Mucosal‐associated invariant T‐cell tumor infiltration predicts long‐term survival in cholangiocarcinoma. Issue 5 (22nd December 2021) - Zimmer, Christine L.; Filipovic, Iva; Cornillet, Martin; O'Rourke, Colm J.; Berglin, Lena; Jansson, Hannes; Sun, Dan; Strauss, Otto; Hertwig, Laura; Johansson, Helene; von Seth, Erik; Sparrelid, Ernesto; et al.
Abstract: Background and Aims: Cholangiocarcinoma (CCA) is a malignancy arising from biliary epithelial cells of intra‐ and extrahepatic bile ducts with dismal prognosis and few nonsurgical treatments available. Despite recent success in the immunotherapy‐based treatment of many tumor types, this has not been successfully translated to CCA. Mucosal‐associated invariant T (MAIT) cells are cytotoxic innate‐like T cells highly enriched in the human liver, where they are located in close proximity to the biliary epithelium. Here, we aimed to comprehensively characterize MAIT cells in intrahepatic (iCCA) and perihilar CCA (pCCA). Approach and Results: Liver tissue from patients with CCA was used to study immune cells, including MAIT cells, in tumor‐affected and surrounding tissue by immunohistochemistry, RNA‐sequencing, and multicolor flow cytometry. The iCCA and pCCA tumor microenvironment was characterized by the presence of both cytotoxic T cells and high numbers of regulatory T cells. In contrast, MAIT cells were heterogenously lost from tumors compared to the surrounding liver tissue. This loss possibly occurred in response to increased bacterial burden within tumors. The residual intratumoral MAIT cell population exhibited phenotypic and transcriptomic alterations, but a preserved receptor repertoire for interaction with tumor cells. Finally, the high presence of MAIT cells in livers of iCCA patients predicted long‐term survival in two independent cohorts and was associated with a favorable antitumor immune signature. Conclusions: MAIT cell tumor infiltration associates with favorable immunological fitness and predicts survival in CCA.